Research Program Planning for Natural Resource Management: A Background Analysis - Agnes C. Rola (Philippine Institute for Development Studies (PIDS), 2000)
Conventionally, agricultural resource management per se is not a popular area of research. Agricultural production research was crop and input specific. Earlier studies recommended fertilizer levels that maximize yields; or cropping patterns that maximize output and profits. Water was considered a fixed input; water productivity was not an issue, so was soil productivity. A review of the results of studies on soil and water conducted in the 1980s and the 1990s showed deficiencies in taking into account the optimal management of these agricultural resources that could have assured sustainable productivity impacts. For soil management for instance, there is a need to unravel that black box of the processes on how farmers decide in agricultural resource management. It is a well known fact that information is the most important input in sustainable agriculture. How do farmers handle this information? What are their knowledge bases? For water management, the issue is about water productivity. This is however, a function of water quantity, quality, and water delivery efficiency. Agricultural decision makers should take active part in the management of the watershed as a significant source of surface water for irrigation. But we also have to guard our shallow groundwater from the environmental pollutants that could affect its utility in agriculture. The current debate by experts on the optimal combination of two sources of irrigation water, i.e. surface water and groundwater, should also be taken into consideration. Finally, the most efficient mode of delivery should be studied. Research on soil and water is numerous. However, the fact that we still observe a lot of resource degradation implies that the desired impact in terms of sustainability outcomes of all these, is not attained. Maybe, a reexamination of the context in which we design soil and water management research agenda, and the process of filtering the results to people who actually use and /or decide on use of the resource is the first item of study. In this regard, an alternative research paradigm for natural resource management (NRM) is proposed. NRM research will go beyond commodities and beyond disciplines. NRM research should be treated from the watershed scale; and take into account the broad range of stakeholders that will be affected and the role of the institutions in the process. Some of the recorded products of research on NRM are actually based on indigenous farmer knowledge. It is only with the building up of the farmer knowledge bases that research can make an impact on farmers practices. Moreover, diagnostics and other farmer/extension friendly kits have to be developed and used as early warning devices. How do farmers learn about these knowledge intensive technologies (KIT)? And also, the role of the various institutions in the promotion or in the constraint to adoption of sustainable technologies should be noted. NRM research is not to be confined to the study of agriculture technologies or the environmental management alone; but rather to the broader, intersectoral linkages that potentially affect farmer behaviour and farmer land use and technology decisions.
Keywords: 330; natural resources and environment; environmental issues; environmental management; Agrarwissenschaft; Natürliche Ressourcen; Philippinen